Pengaruh Pemanfaatan Teknologi Informasi, Penggunanaan Informasi Akuntansi Dan Pelatihan Terhadap Kinerja UMKM Bidang Perdagangan Di Lombok Barat - Muhammad Irfadil; Herawati Khotmi; Elvina Setiawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to determine the effect of the use of information technology, use of accounting information and training on the performance of MSMEs in the Trade Sector in West Lombok. The sample in this study amounted to 96 people. The data collection technique in this research is a questionnaire. The data analysis method uses the Multiple Linear Regression Analysis model. Based on the analysis and results of hypothesis testing, it can be concluded that the information technology utilization variable has a value of tcount (4.000) > tTable (1.661) and a significance value of (0.000) < 0.05. This shows that the use of information technology (X1) has a significant effect on the performance of MSMEs (Y). For the variable use of accounting information, the value of tcount (3.476) > ttable (1.661) and the significance value is (0.000) < 0.05. This shows that the use of accounting information (X2) has a significant effect on the performance of MSMEs (Y). Training variable, tcount value (3.870) > tTable (1.661) and significance value of (0.000) < 0.05. This shows that training (X3) has a significant effect on the performance of MSMEs (Y). The results show that the value of Fcount (6.779) > FTable (3.06) is significant. (0.00) < 0.05, this shows that the variables Use of Information Technology (X1), Use of Accounting Information (X2), and Training (X3) together have a significant effect on the performance of MSMEs (Y).